2013
DOI: 10.1111/apa.12430
|View full text |Cite
|
Sign up to set email alerts
|

Premature infants with birth weights of 1500–1999 g exhibit considerable delays in several developmental areas

Abstract: Premature infants with birth weights of 1500-1999 g exhibited considerable delays in several developmental areas. In addition to biological factors, environmental factors contributed to the reduced scores and/or developmental delays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 20 publications
0
45
1
11
Order By: Relevance
“…Moreover, some authors have confirmed that low birth-weight (between 1,000kg and 1,500Kg) 12 always has a negative impact on language and cognition and that this problem increases on children with very low birth-weight (<1,500Kg), being also responsible for school learning difficulties 1316 .…”
Section: Introduction Prematurity and Language Developmentmentioning
confidence: 99%
“…Moreover, some authors have confirmed that low birth-weight (between 1,000kg and 1,500Kg) 12 always has a negative impact on language and cognition and that this problem increases on children with very low birth-weight (<1,500Kg), being also responsible for school learning difficulties 1316 .…”
Section: Introduction Prematurity and Language Developmentmentioning
confidence: 99%
“…In only 15,8% of researches held in low and middle outcome countries, authors followed-up infants for 2 years or more and less than 50% included studies report on growth outcomes [5,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos evidenciaram que crianças de muito baixo peso são mais vulneráveis para distúrbios do desenvolvimento (OLIVEIRA, ENUMO, 2008;BUHLER, 2008;NOBRE et al, 2009;RIBEIRO et al, 2011;ALMEIDA et al 2013;GUERRA et al 2014). …”
Section: Discussionunclassified
“…Vários autores apresentaram que o risco socioambiental também deve ser considerado no desenvolvimento infantil (SANSAVINI et al, 2011;CASKEY, VOHR, 2013;BROWN et al, 2014;GUERRA et al, 2014;MANSSON et al, 2015). Dentre estes fatores de risco foram citados: baixo nível socioeconômico, escolaridade materna e idade materna (mães muito jovens) (FORMIGA, LINHARES, 2009;SANSAVINI et al, 2011;CASKEY, VOHR, 2013 Tabela 2 e Tabela 3), na comparação GE-I e GC-I e GE-II e GC-II e GE-I e GE-II houve diferença estatística significante no desempenho entre os grupos.…”
Section: Discussionunclassified
See 1 more Smart Citation